Measuring the Quality of Jobs in Turkey - Del Carpio, Ximena V.; Gruen, Carola; Levin, Victoria (World Bank, Washington, DC, 2018)
This paper introduces a new Job Quality Index that measures the quality of jobs in Turkey over the last decade. While the main focus is on wage employment – which in 2016 accounts for nearly 73 percent of all workers – the paper also discusses job quality of the self-employed and unpaid family workers. Based on a comprehensive definition of what constitutes a good job, the index consists of 6 dimensions covering aspects such as adherence to Labor Law regulations, working conditions, adequate linkage between wage and job, productive usage and adaptability of skills, career opportunities and employment resilience. The quality of wage employment improved at the aggregate level from 2009 until 2016; with sharper improvements in job quality between 2009 and 2012. Improvements are largely the result of compositional changes toward more formal sector wage jobs; yet the distribution of job quality remains widespread, across economic sectors, occupational categories and geographic locations. The paper delves deep into each dimension of a good job and highlights the main drivers of good (and bad) jobs in Turkey and identifies the types of reforms that are needed to enable workers to benefit from increasing growth while adapting to changing labor market conditions. Lastly, the findings from this paper show that by measuring job quality policymakers can identify what jobs should be incentivized to ensure that job growth is accompanied by job quality.